The Effects of Restriction Pressures on the Acute Responses to Blood Flow Restriction Exercise - Ilett, Michael J.; Rantalainen, Timo; Keske, Michelle A.; May, Anthony K.; Warmington, Stuart A. (Frontiers in Physiology, 2019)
Purpose No current guidelines or recommendations exist informing the selection of restriction pressure during blood flow restriction exercise (BFRE). Moreover, the effects of specific relative restriction pressures on the acute muscle, metabolic and cardiopulmonary responses to blood flow restriction (BFR) exercise are unclear. The purpose of this study was to characterize these acute responses at different levels of restriction pressure. Methods Participants (n=10) completed rhythmic isometric knee extension exercise across five experimental trials in a balanced randomised order. Three were BFRE trials [B-40 (restriction pressure set to 40% LOP (total limb occlusion pressure)); B-60 (60% LOP); and B-80 (80% LOP)] with a workload equivalent to 20% maximal voluntary force (MCV), one was non-BFRE at 20% MVC (LL) and one was non-BFRE at 80% MVC (HL). Measurements recorded were torque, muscle activity via electromyography (EMG), tissue oxygenation via near infrared spectroscopy, whole body oxygen consumption, blood lactate and heart rate. Results For the LL and B-40 trials, most measures remained constant. However, for the B-60 and B-80 trials, significant fatigue was demonstrated by a reduction in MVC torque across the trial (p < 0.05). Blood lactate increased from baseline in HL, B-60, and B-80 (p < 0.05). Submaximal EMG activity increased in B-60 and B-80 (p < 0.05). Tissue oxygenation decreased in HL, B-40, B-60 and B-80 (p < 0.05), which was lower in the B-80 trial compared to all other trials (p < 0.01). Whole body oxygen consumption was not different between the BFRE trials (p > 0.05). Conclusion We demonstrate graded/progressive acute responses with increasing applied pressure during BFRE, from which we speculate that an effective minimum ‘threshold’ around 60% LOP may be necessary for BFRE to be effective with training. While these data provide some insight on the possible mechanisms by which BFRE develops skeletal muscle size and strength when undertaken chronically across a training programme, the outcomes of chronic training programmes using different levels of applied restriction pressures remain to be tested. Overall, the present study recommends 60% - 80% LOP as a suitable ‘minimum’ BFRE pressure.